Progress in targeting tumor-associated macrophages in cancer immunotherapy - Xia, Wanqiu; Zhang, Xianghan; Wang, Yaru; Huang, Zihan; Guo, Xinyu; Fang, Lei (Frontiers in Immunology, 2025)
Tumor-associated macrophages (TAMs) are central to tumor progression, immune suppression, and resistance to therapy, making them promising targets in cancer immunotherapy. TAMs exhibit functional heterogeneity, polarizing into pro-tumor (M2-like) and anti-tumor (M1-like) phenotypes under different microenvironmental cues. M2-like TAMs promote immune evasion, angiogenesis, and metastasis, while M1-like TAMs enhance antitumor immunity. Combining TAM-targeted therapies with immune checkpoint inhibitors is also emerging as a potential strategy to enhance immunotherapy efficacy. This review outlines TAM-mediated immunosuppression mechanisms, including the secretion of VEGF, TGF-β, and immune checkpoint molecules like PD-L1. We also summarize the current strategies targeting TAMs, such as blocking the CD47/SIRPα axis, using CD40 agonists, and PI3Kγ inhibitors, which have shown promise in preclinical studies. Overall, this review underscores TAMs as pivotal therapeutic targets and proposes future directions to optimize combinatorial immunotherapy for enhanced clinical outcomes.